(untitled) - McBride, Edward J. (Boston, MA., 2006)
The book reinforces and extends what is taught in the students book. Each workbook chapter contains: Contextualized and thematic vocabulary, reading, writing, and grammar activities; A variety of activity types designed for all learning styles; Vocabulary reinforcement opening exercise; A similar structure to the student book with three lessons per chapter, the thrid lesson focusing on workplace skills; Rewiew lessons to synthesize language practiced in the chapter.
Keywords: English language,English language,Life skills; Business English,Problems, exercises, etc.,Problems, exercises, etc